The Foundations of Sufism : An Annotated Translation of Qawāʿid al-Taṣawwuf by Shaykh Aḥmad Zarrūq al-Fāsī (d. 899/1493) - Shams-ur-Rehman, Ghulam, (Middle East and Islamic Studies E-Books Online, Collection 2025., 2025)
Ahmad Zarruq, a 15th-century North African Sufi, turned his considerable intellect towards integrating theology, Islamic law and the spiritual path. His model of a jurisprudentially-grounded Sufism is as relevant today as when he presented it to a mediaeval audience, using an aphoristic style tailored to his educated readership. The current growth of puritanical movements in the Islamic world makes Zarruq's Foundations of Sufism a must-read for scholars, educators and those seeking to reconcile various interpretations of the faith. The author of this fresh translation, an Arabic and Classical Sufism scholar, consulted newly-discovered manuscripts in preparing his critical edition of this seminal work.